The in-vitro effects of 'gamat' extract of stichopus species on human osteoblast cell line - Ahmad, Shahrulazua (2006)
Abstract "Gamat", a local term for sea cucumber, is widely used and had been shown in various studies to have many therapeutic effects. However, its action on osteoblast cells had never been investigated before. Hence, in-vitro study utilising a commercially produced gamat extract of Stichopus sp 1 as the test substance was performed to elucidate the effects on the osteoblast cell line proliferation and functional activity, using MTT colorimetric assay and alkaline phosphatase (ALP) assay respectively. In the preliminary study, osteoblast cells were mixed with a series of two-fold dilutions of gamat concentration in standard culture media from lOOmg/ml down to 1.6mg/ml, and with negative as well as positive controls. Results that were noted after 72 hours incubation period showed an inverse relationship between the gamat concentration and its effect on the osteoblast cell proliferation. The exact ICso was estimated to be approximately 75mg/ml. There was a positive promoting effect of gamat extract on osteoblast cell functional activity when 1.6mg/ml, 3.1mg/ml, 6.2mg/ml, 12.5mg/ml, and 25mg/ml of gamat concentrations were used. Although gamat at 1 OOmg/ml showed thelowest osteoblastic proliferation and functional activity when compared to other concentrations, it was not as cytotoxic as 50% ethanol solution. A follow-up study was subsequently performed by choosing four gamat concentrations namely, I mg/ml, 5 mg/ml, I Omg/ml, and 20mg/ml, to investigate the effect of different incubation periods on the osteoblast cells. For this purpose, the osteoblast cells were first seeded for 24 hours before mixed with the various gamat concentrations and negative control. MTT and ALP assays were carried out after one hour, one day, 3 days, 5 days, and 7 days incubation periods. The results showed that both the osteoblast cell proliferation and functional activity increased as the incubation time increased. However, the effect of each gamat concentration varied with different incubation periods. Most of the time, there was a decrease in osteoblast cell proliferation with an increase gamat concentration. Only gamat concentration at lmg/ml exerted a significant promoting action on the cell proliferation but this was only observed at the 3 days incubation period. Overall, there was a trend showing a relatively greater promoting effect on osteoblast cell functional activity by gamat at 5mg/ml and 1 Omg/ml than the negative control but the significance of this finding was questionable and not consistent at the different incubation periods. In conclusion, the study indicated that whilst the effect of gamat extract on the osteoblast cell functional activity was rather inconsistent, there was strong evidence that gamat decreased the cell proliferation in a concentration-dependent manner.